Analisis Dampak Lingkungan dan Sosial pada UMKM Menggunakan Metode Interpretive Structural Modeling - Hamzah, Dimas; Rizky Pratama, Bayu; Vanny Ravidianti, Nabilla; Yuliawati, Evi (Universitas Negeri Gorontalo, 2025)
Small and Medium Enterprises (SMEs) in Indonesia make a significant contribution to the national economy, particularly in addressing poverty and unemployment. One su`ch SME in Mojokerto, which produces cassava crackers, faces various environmental and social issues in its production process. This study aims to analyze and classify these factors using the Interpretative Structural Modeling (ISM) method. The results of the ISM hierarchical structure analysis show that the factor